A High Programmed Cell Death Protein 1 Hormone Receptor Score on Skin Biopsy is Associated with Sézary Syndrome Diagnosis: A Study of 91 Patients with Erythroderma - Camille Luherne; Sarah Menguy; Thomas Ferte; Marie Beylot-Barry; Julien Seneschal; Brigitte Milpied; Jean-Philippe Vial; Audrey Gros; Samuel Amintas; Béatrice Vergier; Anne Pham-Ledard (Medical Journals Sweden, 2022)
Erythroderma is challenging to diagnose. The aim of this single-centre retrospective study was to identify factors that can be used to improve the diagnosis of erythroderma. Among 91 patients with erythroderma, 21 were diagnosed with eczema, 17 with psoriasis, 20 with drug-induced erythroderma, 13 with erythrodermic mycosis fungoides and 20 with Sézary syndrome. Nail alterations, ear involvement, and severe scaling were significantly associated with psoriasis (p = 0.044). Fever and hypereosinophilia were associated with drug-induced erythroderma. Expression of programmed cell death protein 1 was observed in all skin biopsies. However, with Sézary syndrome, programmed cell death protein 1 expression was significantly higher than with other aetiologies. A programmed cell death protein 1 hormone receptor score (H-score) >50 was associated with Sézary syndrome (p < 0.001, sensitivity 75%, specificity 92%) as well as CXCL13 expression (p < 0.044). CD7 loss was more frequent with erythrodermic mycosis fungoides and Sézary syndrome (p = 0.022). This study reports the importance of programmed cell death protein 1 expression for the differential diagnosis of Sézary syndrome and other aetiologies, including erythrodermic mycosis fungoides.